Effects of Greenshipping to the Maritime Industry - Ogbonnaya, E. A.; Poku, R.; Adigio, E. (Engineering, Technology & Applied Science Research, 2013)
In order to keep focus on the important agenda of sustainability which has lately become an issue of priority, the maritime industry must implement technologies on existing vessels and on those under construction so as to reduce their emissions into the environment. This study examines three potential sources of emission and also identifies a set of emission control measures that are available and could, if fully applied, reduce emission by 19.058%. With the waste heat recovery system, about 2500 kW of energy are saved, thereby increasing the efficiency to 59.11% having about 10.13% gain compared to engines without a waste heat recovery system. It is therefore recommended that the use of waste heat recovery systems should be encouraged on marine vessels to reduce the impact of noxious gasses into the atmosphere.